The Great Trouble : a mystery of London, the blue death, and a boy called Eel - Hopkinson, Deborah (Yearling, 2015)
Eel, an orphan, and his best friend Florrie must help Dr. John Snow prove that cholera is spread through water, and not poisonous air, when an epidemic sweeps across their London neighborhood in 1854.